The Influence of Islamic Financial Literacy and Demographic Factors on Islamic Financial Planning (Case Study in Central Lombok, West Nusa Tenggara) - Heni Susanti; Suharti Suharti; Intan Kusuma Pratiwi (UIN Mataram, 2023)
This study aims to determine the effect of Islamic financial literacy and demographic factors in Central Lombok society both simultaneously and partially on Islamic financial planning. In this study the population is the people of Central Lombok. The sample in this study amounted to 100. Central Lombok community respondents. This research method is quantitative research. The type of research used is causal associative. The data analysis used is SPSS, validity test, reliability test, multiple linear regression, classical assumptions, hypothesis testing, t test, f test and determination test (R2). The results of this study indicate that the Islamic financial literacy variable partially has a positive and significant effect on Islamic financial planning. This can be seen from the t-count value of 17.699 t-table of 1.984 with a significance value of 0.001 0.05. Demographic factor variables partially have a positive and significant effect on Islamic financial planning. This can be seen from the t-count value of 12.699> t-table of 1.984with a significance value of 0.001<0.05. While simultaneously obtained the value of f-count 232.524and f-table 3.09 has a positive and significant effect on Islamic financial planning with a f-count value of 232.524,3.09 f-table and a significant probability value of 0.001<0.05. So it can be concluded that the variable (X1) (X2) simultaneously significant effect on (Y).